Expanding the phenotypic and imaging spectrum of GFPT1-related congenital myasthenic syndromes: a Brazilian case series - Camelo-Filho, Antonio Edvan; Gomes, Gustavo Rodrigues Ferreira; Lima, Pedro Lucas Grangeiro Sá Barreto; Peixoto, Vitória Maria Torres; Mariano, Tamiris; Lopes, Ellen Mourão Soares; Alencar, Raquel Diógenes; Nóbrega, Paulo Ribeiro; Pessoa, André Luiz Santos (Frontiers in Neurology, 2025)
IntroductionGFPT1-related congenital myasthenic syndrome (CMS) is a rare, autosomal recessive disorder that impairs neuromuscular transmission due to defective glycosylation of the neuromuscular junction. While typically presenting with limb-girdle weakness, tubular aggregates on biopsy, and a favorable response to acetylcholinesterase inhibitors, the full phenotypic and imaging spectrum remains incompletely defined.MethodsWe evaluated five Brazilian patients from two unrelated families, all with pathogenic variants in homozygosity in GFPT1 c.41G>A (p.Arg14Gln). Clinical, electrophysiological, and imaging assessments included nerve conduction studies, electromyography, repetitive nerve stimulation (RNS), and muscle ultrasound graded using the modified Heckmatt scale. Functional severity was estimated using the Myasthenia Gravis Foundation of America (MGFA) classification.ResultsAll patients showed early-onset proximal weakness, distal lower limb weakness, and frequent falls. One patient exhibited atypical features, including neonatal onset epilepsy, and cognitive impairment. RNS revealedmarked decrements in proximal upper-limb muscles (deltoid 43.6%, trapezius 37.3%) and in the distal lower-limb tibialis anterior (36.5%), consistent with foot dorsiflexion weakness. Muscle ultrasound revealed varying degrees of myopathic echogenicity. A strong positive correlation was found between MGFA severity and mean Heckmatt score (p = 0.028), suggesting alignment between functional severity and muscle structural changes.DiscussionOur findings expand the clinical spectrum of GFPT1-CMS to include possible central nervous system involvement and demonstrate the value of integrating electrophysiology and muscle ultrasound into diagnostic evaluation. Muscle ultrasound may serve as a structural biomarker for phenotypic stratification in CMS, and distal involvement—particularly foot dorsiflexion weakness—represents an additional diagnostic clue for GFPT1-CMS.